Bending Test Analysis of Hybrid GLARE Material Using Nano Adhesive CNT and Aluminum Powder Reinforcement - Muh Anhar; Ferry Setiawan; Faradiba Septiane; Dhimas Wicaksono (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2025)
The use of composites as materials has developed rapidly due to the many advantages they offer compared to alternative engineering materials. In this study, the researchers used Glass Laminated Aluminium Reinforced Epoxy (GLARE) to analyze the results of bending tests on hybrid laminate composites reinforced with fiberglass and aluminum plates. The method used was vacuum bagging, and the sample was reinforced with epoxy resin combined with carbon nanotube (CNT) nanoparticles and aluminum (AL) powder. This study applied variations in resin as adhesive, surface treatments, and the addition of CNT and AL nanopowders to determine their effects on the bending strength of the composite. The results showed that specimens with surface treatment and nanoparticle additions had higher bending strength compared to those without nanoparticles or surface treatment. The highest bending stress was found in the CNT variation specimens, with an average value of 181.4158 MPa. The lowest average bending stress was observed in the plain specimens without nanoparticles and surface treatment, with a value of 151.766 MPa. Macro photo analysis after the bending test showed adhesive failure in the plain variation (no resin adhered to the aluminum surface), and cohesive failure in the CNT variation (resin adhered to the treated aluminum surface). These findings indicate that the addition of nanoparticles improves bending strength. This research plays an important role in understanding the influence of nano adhesives and nanoparticles on the bending strength of hybrid laminate composites.